Im Horizont des Dialogs: zur Entwicklung evangelisch-theologischer Versöhnungslehre und ihrem Beitrag zu interkonfessioneller und interreligiöser Verständigung - Nüssel, Friederike (Christology revised, 2024)
To further peace and justice and to shape a process of reconciliation is the essential goal of the modern ecumenical movement of the churches and their inter-religious dialogue. And yet, what is to be understood by reconciliation and how can it, despite differing conceptions, result in peace and justice? This question is in no way answered in Christian theologies in a unified way. In this lecture, I will be concerned with working out a Christian understanding of reconciliation which, on the one hand, accentuates the specifically Christian concern and, on the other, can count as a contribution to inter-religious conversation about reconciliation.
Gesehen am 30.01.2024